2017
DOI: 10.5194/amt-2017-378
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quality assessment of the Ozone_cci Climate Research Data Package (release 2017): 1. Ground-based validation of total ozone column data products

Abstract: Abstract. The GOME-type Total Ozone Essential Climate Variable (GTO-ECV) is a Level-3 data record, which combines 15 individual sensor products into one single cohesive record covering the 22 year period from 1995 to 2017, generated in the frame of the European Space Agency's Climate Change Initiative Phase-II. It is based on Level-2 total ozone data produced by the GODFIT v4 algorithm as applied to the GOME/ERS-2, OMI/Aura, SCIAMACHY/Envisat and GOME-2/MetopA and /MetopB observations. In this paper we examine… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…This, therefore, provides confidence in the result that there is little net change in total column ozone since 1998. Additionally, Chehade et al (2014) reported that other total column ozone composites agree very well with the SBUV total column ozone and there is little difference between the various total column ozone composites when performing trend analysis (see also Garane et al, 2017).…”
Section: Tropospheric Ozone Contribution To Total Column Ozonementioning
confidence: 99%
“…This, therefore, provides confidence in the result that there is little net change in total column ozone since 1998. Additionally, Chehade et al (2014) reported that other total column ozone composites agree very well with the SBUV total column ozone and there is little difference between the various total column ozone composites when performing trend analysis (see also Garane et al, 2017).…”
Section: Tropospheric Ozone Contribution To Total Column Ozonementioning
confidence: 99%